Financial Management Practices and Financial Accounting Standards Compliance Among Micro and Small Enterprises in Selected Cities of Cavite - Singson, Nicole Ashley; Bigalbal, Elizabeth D.; Ilagan, Florindo C.; Sustrina, Maria Isolde R.; Desepida, Maria Cristina L.; Corpuz, Jaysi T.; Arayata, Sophia Marie; Paraiso, Kyle Raine; Digal, Cyren Jade S.; Lurcha, Kim Aaron; Bacotoy, Jannah Marie; Abutin, Hazel Jhem; Cabacungan, Crissamiene Nazarre C.; Fidel, Betsy Rose S. (Future Science / FSH-PH Publications, 2026)
This study examined the relationship between Financial Management Practices (FMP) and compliance with Financial Accounting Standards (FAS) among Micro and Small Enterprises (MSEs) in Dasmariñas, Imus, and General Trias, Cavite. It provides insights into how MSEs can enhance their financial practices and accounting compliance to achieve microenterprises sustainability and accurate financial reporting. A descriptive-correlational research design was employed, utilizing primary data collected from 384 Department of Trade and Industry (DTI) registered MSE owners and managers through online and printed questionnaires. Responses were measured using a four-point Likert scale, and the relationship between FMP and FAS compliance was analyzed using Spearman’s Rho correlation. The results showed that MSEs exhibited a high level of financial management practice and a high degree of compliance with financial accounting standards. Inventory management emerged as the most frequently practiced FMP, while the Statement of Profit or Loss (SPL) was the most prepared financial statement. When grouped according to business profile, no significant differences were found in the level of FMP implementation or FAS compliance. However, a strong and statistically significant positive relationship was observed between FMP and FAS compliance. In conclusion, the findings indicate that effective financial management practices contribute to higher levels of compliance with financial accounting standards among MSEs, regardless of business profile. MSEs that consistently apply sound financial management practices are more likely to produce accurate and reliable financial statements.